2018
DOI: 10.5539/jas.v10n3p162
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sugar Beet Tops and Prebiotic Effect on Nutrient Digestibility, Caecal Activity and Organ Histology of Weaning Rabbits

Abstract: The current study was designed to evaluate the effect feeding weaning rabbits sugar beet tops (SBT) with prebiotic on digestibility of nutrients and caecal microbial activity, volatile fatty acids estimation and organs histology. Fifty four 6-week-old unsexed weaning NZW rabbits were randomly distributed in a factorial (3 × 2) design to six equal groups. Sugar beet tops (SBT) was used at levels 0.0, 20 or 30% of the diet instead of the percent of alfalfa hay in the control diet in presence of 1.0 g/kg diet or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Abo El-Maaty et al (2018) reported that dietary prebiotic had a positive effect on the digestibility coefficients of DM, OM, CP, EE, CF and NFE of growing rabbits. They also noticed that added prebiotic had a positive effect on caecal fermentation activities of growing rabbits.…”
Section: Effect Of Feed Supplementsmentioning
confidence: 99%
“…Abo El-Maaty et al (2018) reported that dietary prebiotic had a positive effect on the digestibility coefficients of DM, OM, CP, EE, CF and NFE of growing rabbits. They also noticed that added prebiotic had a positive effect on caecal fermentation activities of growing rabbits.…”
Section: Effect Of Feed Supplementsmentioning
confidence: 99%
“…The effect of SSF sorghum on ce be a response to increased nutrient availability due to sorghum pre-hydr digestion retention time in the caecum is relatively short, it is mainly the fermentable cell wall polysaccharides (such as the hemicellulose fraction) tha at this point, playing a key role not only in rabbit digestive processes but gestive health and sanitary status of rabbits [7,37]. T1-supplied rabbits exh crypts in all gut tracts except for the colon (p ≤ 0.05), probably due to the incre in nutrient absorption, which is mainly attributable to the dietary fibers tha able after the pretreatment with white-rot fungi and their lignocellulolytic plexes [36,38]. Thus, supplementing growing rabbit diets with sorghum al SSF with T. maxima CU1 and P. sanguineus CS2 might contribute to incre transit time, improve mucosal functionality, and modulate their microbiot vestigations will be performed to explore these issues.…”
Section: Effects On Intestinal Morphologymentioning
confidence: 99%
“…These results are in accordance with those obtained by Ali and El-Saidy (2003) concluded that DSBT could be used successfully as a replacer to 50% from BH in ration of growing lambs without any detritus effects on productive performance. Abo El-Maaty et al (2017 and2018) found that the digestibility coefficients of dry matter (DM), crude protein (CP), ether extract (EE) and NFE of 12-week old NZW rabbits were improved by feeding diets containing SBT. Bendary et al (2000) reported that no significant differences among experimental ration in digestibility coefficient of all nutrients when cow fed rations containing different forms of sugar beet tops and berseem silage compared with those fed dry summer ration.…”
Section: -Nutrients Digestibility Coefficientsmentioning
confidence: 99%